Dynamics of Vascular Protective and Immune Supportive Sphingosine-1-Phosphate During Cardiac Surgery - Greiwe, Gillis; Moritz, Eileen; Amschler, Katharina; Poppe, Annika; Sarwari, Harun; Nierhaus, Axel; Kluge, Stefan; Reichenspurner, Hermann; Zoellner, Christian; Schwedhelm, Edzard; Daum, Günter; Tampe, Björn; et al. (Frontiers in Immunology, 2021)
Introduction: Sphingosine-1-phosphate (S1P) is a signaling lipid and crucial in vascular protection and immune response. S1P mediated processes involves regulation of the endothelial barrier, blood pressure and S1P is the only known inducer of lymphocyte migration. Low levels of circulatory S1P correlate with severity systemic inflammatory syndromes such as sepsis and shock states, which are associated with endothelial barrier breakdown and immunosupression. We investigated whether S1P levels are affected by sterile inflammation induced by cardiac surgery. Materials and methods: In this prospective observational study we included 46 cardiac patients, with cardiopulmonary bypass (CPB, n=31) and without CPB (off-pump, n=15). Serum-S1P, S1P-sources and carriers, von-Willebrand factor (vWF), C-reactive protein (CRP), procalcitonin (PCT) and interleukin-6 (IL-6) were measured at baseline, post-surgery and at day 1 (POD 1) and day 4 (POD 4) after surgical stimulus. Results: Median S1P levels at baseline were 0.77 nmol/mL (IQR 0.61-0.99) and dropped significantly post-surgery. S1P was lowest post-surgery with median levels of 0.37 nmol/mL (IQR 0.31-0.47) after CPB and 0.46 nmol/mL (IQR 0.36-0.51) after off-pump procedures (P0.001). The decrease of S1P was independent from surgical technique and observed in all individuals. In patients, in which S1P levels did not recover to preoperative baseline ICU stay was longer and severity of postoperative inflammation was more severe. S1P levels are associated with its sources and carriers and vWF, as a more specific endothelial injury marker, in different phases of the postoperative course. Determination of S1P levels during surgery suggested that also the anticoagulative effect of heparin might influence systemic S1P. Discussion: In summary, serum-S1P levels are disrupted by major cardiac surgery. Low S1P levels post-surgery may play a role as a new marker for severity of cardiac surgery induced inflammation. Due to well-known protective effects of S1P, low S1P levels may further contribute to the observed prolonged ICU stay and worse clinical status. Moreover, we cannot exlude a potential inhibitory effect on circulating S1P levels by heparin anticoagulation during surgery, which would be a new pro-inflammatory pleiotropic effect of high dose heparin in patients undergoing cardiac surgery.